'Shepherding a leopard': Football, masculinities and the spatial politics of xenophobia among Zimbabwean male migrants in Stellenbosch. Issue 2 (2nd April 2016) - Leslie Mangezvo, Pedzisayi
Abstract: In this article I focus on an all-Zimbabwean football team in Stellenbosch, South Africa. I draw on 15 months of conversations with Zimbabwean male migrants to explore discourses of migrancy and gender transformations, migrant associations, football and the expression, negotiation and assertion of particular masculinities. The analysis is done through the prism of the team's composition and its playing circuits, which reflect migrant efforts to integrate in an environment they characterise as conflictual. I examine the link between real and imagined threat of exclusion, and the fashioning of socio-spatial separations between the study participants and South African nationals. I argue that closer attention to the football, and the manner in which it is played, provides important insights into how Zimbabwean migrants think of themselves through the sport, bearing in mind that transnational migration fractures dominant and popular conceptions of gender. The perceived threat of xenophobia, through football, creates fleeting solidarities among the study participants. However, these belie the numerous intra-group rivalries along class, sexuality, ethnic and linguistic lines. It is ironic, therefore, that a space ostensibly created to deal with the fear of otherness itself becomes a site for the exclusion of specific categories of Zimbabwean migrants. I deploy the notion of 'tactical cosmopolitanism' to draw insights into the problematic of the study participants' insertion into their host communities.